MODELLING OF ASSEMBLY PROCESS MODULES IN TERMS OF MASS CUSTOMIZED MANUFACTURING - Bednar, Slavomir; Modrak, Vladimir (Advanced Logistic Systems - Theory and Practice, 2016)
In todayʼs market, personalized demands of various groups typical for mass customization (MC) phenomena can be satisfied only through the strategy of mass customized manufacturing. Even though mass customization as a strategic tool to satisfy individual requirements of customers is under theoretical exploration for many years, theory of mass customized manufacturing is at the beginning. The main objective of this paper is to outline possible framework for quantification of variety-induced complexity based on enumeration of all possible product configurations identified in a single assembly process module.